Adjuvant radiotherapy after breast conserving surgery – A comparative effectiveness research study. Issue 1 (January 2015) - Corradini, Stefanie; Niyazi, Maximilian; Niemoeller, Olivier M.; Li, Minglun; Roeder, Falk; Eckel, Renate; Schubert-Fritschle, Gabriele; Scheithauer, Heike R.; Harbeck, Nadia; Engel, Jutta; Belka, Claus
Abstract Purpose The purpose of this retrospective outcome study was to validate the effectiveness of postoperative radiotherapy in breast conserving therapy (BCT) and to evaluate possible causes for omission of radiotherapy after breast conserving surgery (BCS) in a non-trial population. Methods Data were provided by the population-based Munich Cancer Registry. The study included epidemiological data of 30.811 patients diagnosed with breast cancer from 1998 to 2012. The effect of omitting radiotherapy was analysed using Kaplan–Meier-estimates and Cox proportional hazard regression. Variables predicting omission of radiotherapy were analysed using multivariate logistic regression. Results Use of postoperative radiotherapy after BCS was associated with significant improvements in local control and survival. 10-year loco-regional recurrence-free-survival was 90.8% with postoperative radiotherapy vs. 77.6% with surgery alone (p < 0.001). 10-year overall survival rates were 55.2% with surgery alone vs. 82.2% following postoperative radiotherapy (p < 0.001). Variables predicting omission of postoperative radiotherapy included advanced age (women ⩾80 years; OR: 0.082; 95% CI: 0.071–0.094, p < 0.001). Conclusions This study shows a decrease in local control and a survival disadvantage if postoperative radiotherapy after breast conserving surgery is omitted in an unselected cohort of primary breast cancer patients. Due to its epidemiological nature, it cannot answer the question in whom postoperative radiotherapy can be safely omitted.